Wild Cordyceps sinensis exhibits far lower arsenic accumulation and hepatorenal toxicity in mice compared to equivalent dose of inorganic arsenic - Gao, Liang; Yang, Hongxia; Ma, Jinmei; Bi, Hongtao; Xiao, Yuancan; Li, Cen; Wei, Lixin (Frontiers in Pharmacology, 2025)
IntroductionWild Cordyceps sinensis (C. sinensis) is a Chinese medicinal material known for its renal and pulmonary benefits. However, inorganic arsenic in wild Cordyceps sinensis may accumulate in the body following prolonged consumption; therefore, rigorous safety evaluations are needed.MethodsThis study compared the impacts of wild Cordyceps sinensis at the maximum clinical dose and equivalent doses of inorganic arsenic (16.36 mg/kg) to its total arsenic dose on organ indices, arsenic accumulation, and functional and pathological changes in the liver and kidney in mice, aiming to explore the safety of consuming wild Cordyceps sinensis. Arsenic accumulation in organs was measured via ICP–MS, while serum markers of liver and kidney functions were assessed via ELISA and biochemical assay kits. Histopathology was observed through H&E staining.ResultCompared with those in the control group, no significant adverse effects on body weight, organ indices, arsenic accumulation, liver or kidney function, or liver or kidney pathology were observed in the Cordyceps group. In contrast, inorganic arsenic exposure resulted in significant arsenic accumulation in organs, especially in the liver and kidneys (p < 0.01), liver and kidney function impairment (p < 0.01), and pathological changes, including hepatic steatosis, mild edema, balloon degeneration, and renal tubular epithelial cell edema and degeneration, with the aggregation of eosinophils in the renal capsule.ConclusionThese findings indicate that, at the maximum clinical dose, wild Cordyceps sinensis does not cause measurable hepatorenal toxicity in long-term and exhibits markedly greater safety compared to a mixture of inorganic arsenic compounds (sodium arsenate and sodium arsenite) at an equivalent total arsenic dose.